MODEL APPLICATION CONTEXTUAL TEACHING AND LEARNING LEARNING TO IMPROVE SKILLS CLASS DESCRIPTION WRITE ESSAYS IV SD STATE 66 PEKANBARU - Iza Komala Sari Iza Komala Sari; Hamizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: The problem underlying this study is the low average grade in essay writing the description in the language lesson is 64.83.. This is due, students just sit passively receive information and see what exemplified teacher, the teacher does not connect with the experience of learning materials to the environment , and monotonous learning process so as to make students become bored. This study aims to improve essay writing skills through learning model description Contextual Teaching Learning (CTL) in the fourth grade students of SD Negeri 66 Pekanbaru. This study design using classroom action research conducted in two (2) cycles with 4 (four) stages:  planning,  action, observation and reflection as a basis for re-planning the next cycle. From this research, the essay writing skills descriptions of UH Iin the first cycle average-rata76,19 increased 17.52%. While in the second cycle UH II increased to 80, an increase from baseline of 23.39%. The results of the data analysis activities of the first meeting of teachers first cycle with a percentage of 50% with (category enough). The second meeting of the first cycle with a percentage of 62.5% (fair category). The first meeting of the second cycle with the percentage of 81.25% (both categories) and the second meeting of the second cycle with the percentage of 93.75% (very good category). While the activities of students first encounter the first cycle with the percentage 46.87% (less category). The second meeting of the first cycle with the percentage of 59.37% (fair category).  At the first meeting of the second cycle with the percentage of 75% (both categories) and the second meeting of the second cycle with the percentage of 93.75% (very good category).  From the results of this research can be concluded that the application of the learning model contextual teaching and learning can improve essay writing skills description Elementary School fourth grade students 66 Pekanbaru Keywords: Contextual Teaching Learning Model, and Authorship Description